Surface treatment for antibacterial applications - Janet, Kezia (Nanyang Technological University, 2022)
With the ongoing pandemic, wearing masks has become a part of our daily life. Masks have played an essential role as they have become a necessary thing for us in doing varying activities. Hence, in addition to the importance of protection that the masks can provide, one should also take into consideration the comfort of users upon wearing the masks. Different research has been conducted to improve the protection for users, for instance through additional functionalities to kill viruses and bacteria, not only trapping them. Moreover, incorporating these functionalities to reusable masks is a field of interest, as currently, the usage of disposable masks has created a newly emerging issue of waste to the environment.